Cognitive control in adults with high-functioning autism spectrum disorder: a study with event-related potentials - Möde, Laura; Borgolte, Anna; Ghaneirad, Erfan; Roy, Mandy; Sinke, Christopher; Szycik, Gregor R.; Bleich, Stefan; Wiswede, Daniel (Frontiers in Psychiatry, 2023)
Introduction Little is known about cognitive control in adults with high-functioning forms of autism spectrum disorder because previous research focused on children and adolescents. Cognitive control is crucial to monitor and readjust behavior after errors to select contextually appropriate reactions. The congruency effect and conflict adaptation are measures of cognitive control. Post-error slowing, error-related negativity and error positivity provide insight into behavioral and electrophysiological correlates of error processing. In children and adolescent with autism spectrum disorder deficits in cognitive control and error processing have been shown by changes in post-error slowing, error-related negativity and error positivity in the flanker task. Methods We performed a modified Eriksen flanker task in 17 adults with high-functioning autism spectrum disorder and 17 healthy controls. As behavioral measures of cognitive control and error processing, we included reaction times and error rates to calculate congruency effects, conflict adaptation, and post-error slowing. Event-related potentials namely error-related negativity and error positivity were measured to assess error-related brain activity. Results Both groups of participants showed the expected congruency effects demonstrated by faster and more accurate responses in congruent compared to incongruent trials. Healthy controls exhibited conflict adaptation as they obtained performance benefits after incongruent trials whereas patients with autism spectrum disorder did not. The expected slowing in reaction times after errors was observed in both groups of participants. Individuals with autism spectrum disorder demonstrated enhanced electrophysiological error-processing compared to healthy controls indicated by increased error-related negativity and error positivity difference amplitudes. Discussion Our findings show that adults with high-functioning autism spectrum disorder do not show the expected upregulation of cognitive control in response to conflicts. This finding implies that previous experiences may have a reduced influence on current behavior in these patients which possibly contributes to less flexible behavior. Nevertheless, we observed intact behavioral reactions after errors indicating that adults with high-functioning autism spectrum disorder can flexibly adjust behavior in response to changed environmental demands when necessary. The enhancement of electrophysiological error-processing indicates that adults with high-functioning autism spectrum disorder demonstrate an extraordinary reactivity toward errors reflecting increased performance monitoring in this subpopulation of autism spectrum disorder patients.